The Cellular Uptake, Distribution and Toxicity of Poly (lactic-co-glycolic) Acid Nanoparticles in Medicago sativa Suspension Culture - Ulusoy, Esma; Derman, Serap; Erisen, Semiha (ARS DOCENDI, 2020)
Nanoparticle systems can be used for agricultural purposes including for risk analysis, application of pesticides or fertilizer, and improving gene transfer technology. Here, the entrance of Fluorescein isothiocyanate isomer I (FITC)-loaded poly (lactic-co-glycolic) acid (PLGA) nanoparticles (NPs) into a Medicago sativa (alfalfa) cell suspension by sonication was studied as a model system for gene transfer in plants. The single emulsion solvent evaporation method was used to synthesis of nanoparticles. Particle size, zeta potential and polydispersity index of nanoparticles were measured and morphological investigation was carried out for nanoparticle characterization. The cytotoxic and genotoxic effects of PLGA NPs were determined on alfalfa cells using 3-(4,5-dimethylthiazol-2-yl)2,5-diphenyltetrazolium bromide (MTT) and comet assay, respectively. Ultrasound application increases the cellular uptake of PLGA NPs. The best result (82.66%) was obtained at 3 min of sonication. Transmission Electron Microscopy (TEM) analyses showed that PLGA NPs up to 100 nm passed through the cell wall and were distributed into the cytoplasm and nucleus. Furthermore, a cytotoxic and genotoxic effect was not observed in the cultured cells exposed to PLGA NPs by sonication. Thus, PLGA NPs system could be used in various agricultural systems in plants. This protocol is an alternative and safe method for gene transfer in plants.
Keywords: Medicago sativa; nanoparticles; PLGA; suspension cell culture; sonication; PLGA NANOPARTICLES; GENE DELIVERY; CELLS; NANOMATERIALS; MEMBRANE; Biotechnology & Applied Microbiology